Feminicídio em pauta: Uma análise de discurso de crimes que ganharam destaque no telejornal Correio Verdade - Rosas, Felícia Arbex (2021)
This study analyses the speech of femicide crimes that got emphasis on local news and got aired at noon by the "TV Correio", "Rede Record's affilitate. This study analysed the kind of speech and approaches are presented by the show focusing on questions like: How is this type of crime narrated to the public? Does it reinforce the male chauvinist speech of women submission? The two cases selected got aired on April the 8th and 16th, 2019. Year that according to studies reached the peack on this kind of crime on the state of Paraiba since the law got created in the country. The law 13.104/2015, punishes disregard towards women, discrimination towards women conditions and mainly punishment to murder.These cases got space on TV due to the level of brutallity and also because in one of them the victim was very popular on her community. The methodology applied was the french school of speech analyses that allowed us to study the text and contextualize the speech of the reporter, the people that got interviewed and the main footages displayed on these news. Understanding that the way the midia shows the news on TV can contribute to the non nomarlization of this kind of gender violence. Concepts about sensationalist journalism, feminicide and media and how an event become news are addressed in this study. During this study we got contributions from: Patrick Charaudeau (2006), Eni Orlandi (1999), Heleieth Saffioti (2015), Eva Blay (2008) ; Pierre Bourdieu (2002) Marcia Tiburi (2019), Ana Paula Portella (2020), Prado e Saneamatsu (2017); Mauro Wolf (2001), Nelson Traquina (2005), João Canavilhas (2009) e Daniel Angrimani (1995) e José Arbex (2002). This research shows that using a sensacionalist approach , "Correio Verdade" spreads the male chauvinist, moralist and religious speech not mentioning at any moment words like: femicide or violence against women" helping normalize the murder of innocent women".